2022
DOI: 10.3389/fncir.2022.957441
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of cholinergic activity in the septo-hippocampal system

Abstract: Cholinergic projection neurons in the medial septum and diagonal band of Broca are the major source of cholinergic modulation of hippocampal circuit functions that support neural coding of location and running speed. Changes in cholinergic modulation are known to correlate with changes in brain states, cognitive functions, and behavior. However, whether cholinergic modulation can change fast enough to serve as a potential speed signal in hippocampal and parahippocampal cortices and whether the temporal dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…However, speed signals could also come from inhibitory INs [ 51 ], and a near real-time accurate speed code by firing rate may require fast-spiking INs [ 52 , 53 ]. Another alternative or complementary source of speed signal could come from the correlation of speed with theta rhythms [ 29 , 53 ] and related cholinergic [ 23 ] or glutamatergic [ 54 , 55 ] input from the medial septum. Expanding this SNN implementation of the CAN to include those additional mechanisms might help shed light on their computational plausibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, speed signals could also come from inhibitory INs [ 51 ], and a near real-time accurate speed code by firing rate may require fast-spiking INs [ 52 , 53 ]. Another alternative or complementary source of speed signal could come from the correlation of speed with theta rhythms [ 29 , 53 ] and related cholinergic [ 23 ] or glutamatergic [ 54 , 55 ] input from the medial septum. Expanding this SNN implementation of the CAN to include those additional mechanisms might help shed light on their computational plausibility.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hippocampal ACh release in an animal placed in a novel environment has two components, one related to novelty, that disappears in a familiar environment ( Thiel et al, 1998 ), and one related to motor activity, associated with increased exploration ( Giovannini et al, 2001 ). Indeed, a recent fiber photometric study showed that part of the population activity in medial septal cholinergic neurons is correlated with the logarithm of running speed ( Kopsick et al, 2022 ). We are primarily interested in the component of the ACh signal related to novelty because of previous studies demonstrating modulation of place cell firing that was more pronounced during the first day in a novel environment ( Roth et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural exploration in rodents is associated with hindlimb rearing which is thought to be important for memory encoding (Layfield et al, 2023). Cholinergic tone is elevated during novel exploration including during periods of behavioural rearing (Acquas et al, 1996;Giovannini et al, 2001;Kopsick et al, 2022;van Abeelen, 1989). In this issue, Cassity et al (2024) utilized optogenetic inhibition of the medial septum to identify whether cholinergic activity promotes exploratory behaviour or whether it acts in concert with exploration to enhance spatial information encoding.…”
Section: Medial Septum Cholinergic Signalling -Novel Implications For...mentioning
confidence: 99%